Dead silence : a Body finder novel - Derting, Kimberly (Harper, an imprint of HarperCollinsPublishers, 2013)
"When Violet, a high school senior, learns that an underground group has been carrying out murders on the order of their Charles Manson-like leader, she is pulled into a deadly hunt, where even her ability may not save her"--